POLA MAKAN DAN MEROKOK SEBAGAI FAKTOR RESIKO KEJADIAN HIPERTIROID - , Munifa ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Hypertyroid is also known as tyrotoxicosis. Hypertyroidism can be defined as response of physiological tissue to effect of excessive thyroid metabolic hormone. This condition can appear suddenly or due to excessive treatment thyroid hormone for patient hypothyroid. There are two types of spontaneous hyperthyroidism most commonly found